Bovine subclinical mastitis reduces milk yield and economic return - Gonçalves, J.L.; Kamphuis, C.; Martins, C.M.M.R.; Barreiro, J.R.; Tomazi, T.; Gameiro, A.H.; Hogeveen, H.; dos Santos, M.V. (Livestock science, 2018)
The effect of different pathogens was studied by evaluating the contralateral (healthy and infected) mammary quarters of 146 lactating cows. The impact of SM on economic return (quarter milk yield × milk price) was determined by applying milk payment estimates on milk collected from healthy vs. infected glands. Cows were considered infected when they had at least 2 out of 3 weekly composite SCC results > 200 × 103 cells/mL and a microbiological culture (MC) positive result from composite foremilk samples, collected in the third week of sampling. Infected cows were evaluated a second time within 15 days and had milk yield measured at the quarter level and foremilk samples collected by aseptic technique for analysis of MC, milk composition and SCC. Of the 611-composite milk samples, 397 (65%) were culture-negative, and 214 (35%) were culture-positive and the most frequent isolated bacteria were Corynebacterium spp. (7.9%), coagulase negative staphylococci (5.8%), Staphylococcus aureus (5.3%), Streptococcus uberis (4.6%), Streptococcus agalactiae (3.9%), other environmental streptococci (2.4%), Gram-negative isolates (2.4%), Enterococcus spp. (1.4%) and Streptococcus dysgalactiae (0.7%). A total of 55 pairs of healthy contralateral quarters (control) were compared, and no difference was observed between them when evaluating SCC, milk yield, fat and protein concentration and economic return. A total of 124 pairs of healthy had lower SCC (274.9 × 103 cells/mL) than infected contralateral quarters (SCC of 1038.5 × 103 cells/mL). At the quarter level, IMI caused by minor pathogens had no effect on SCC, milk yield and economic return. Subclinical mastitis caused by contagious and environmental pathogens increased SCC and decreased milk yield when compared with healthy contralateral quarters. Moreover, quarters infected by contagious pathogens had increased concentrations of milk protein and fat when compared with healthy contralateral quarters. Therefore, the milk economic return was lower in quarters with SM caused by environmental pathogens (US$ 0.18/quarter.milking) and contagious (US$ 0.22/quarter.milking) when compared with healthy contralateral quarters. The milk losses ranged from 0.07 kg/quarter.milking to 1.4 kg/quarter.milking and the economic losses ranged from US$ 0.02–0.4/quarter.milking according to the pathogen causing SM. •Subclinical mastitis (SM) caused by specific groups of pathogens results in distinctive degrees of changes of milk yield and composition.•Comparing healthy and infected contralateral mammary quarters can minimize confounding factors such as the cow’s immune status at the time of infection, management systems or environmental challenge.•The milk losses ranged from 0.07 to 1.4 Kg/quarter.milking according to the pathogen causing SM.•Milk economic return was lower in quarters with SM when compared with healthy contralateral quarters.